2012
DOI: 10.1016/j.cell.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Auditory Organ Genes and Genetic Hearing Defects

Abstract: The Drosophila auditory organ shares equivalent transduction mechanisms with vertebrate hair cells, and both are specified by atonal family genes. Using a whole-organ knockout strategy based on atonal, we have identified 274 Drosophila auditory organ genes. Only four of these genes had previously been associated with fly hearing, yet one in five of the genes that we identified has a human cognate that is implicated in hearing disorders. Mutant analysis of 42 genes shows that more than half of them contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
244
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(262 citation statements)
references
References 97 publications
9
244
0
Order By: Relevance
“…While our work is the first description of this opsin expression pattern in mollusks, opsin-expressing mechanoreceptors have been recently described in the annelid Platynereis, zebrafish and Drosophila (Backfisch et al, 2013;Senthilan et al, 2012). From work on mechanoreception in Drosophila antennae, we now know that opsin is required for anntenal mechanoreceptors to detect vibrations, highlighting a previously unknown role for opsin in senses besides light detection (Senthilan et al, 2012). We do not yet know whether the opsin-expressing cells we found in hatchling O. bimaculoides skin function as mechanoreceptors, light sensors or both, or the extent to which opsin is required for detecting either of these stimuli.…”
Section: Discussionmentioning
confidence: 89%
“…While our work is the first description of this opsin expression pattern in mollusks, opsin-expressing mechanoreceptors have been recently described in the annelid Platynereis, zebrafish and Drosophila (Backfisch et al, 2013;Senthilan et al, 2012). From work on mechanoreception in Drosophila antennae, we now know that opsin is required for anntenal mechanoreceptors to detect vibrations, highlighting a previously unknown role for opsin in senses besides light detection (Senthilan et al, 2012). We do not yet know whether the opsin-expressing cells we found in hatchling O. bimaculoides skin function as mechanoreceptors, light sensors or both, or the extent to which opsin is required for detecting either of these stimuli.…”
Section: Discussionmentioning
confidence: 89%
“…Surprisingly, when we compared this set of transcripts with the recently identified auditory gene set consisting of 274 genes, we found a significant overlap of 58 genes (representation factor 2.5, P < 7.661e-11; Table S1) (21). This observation further suggested that hearing might play a prominent role in Drosophila aggression.…”
Section: Functional and Genetic Disruption Of The Sound-sensitive Ab mentioning
confidence: 85%
“…From the overlapping genes, we selected a cohort of signal transduction genes with reported hearing defects for further analyses: the transient receptor potential (TRP) channel genes nan (nanchung), iav (inactive), and trpl (transient receptor potential-like) and the Ca 2+ signaling-related genes Arr2 (arrestin 2) and inaD (inactivation no afterpotential D) (21). We also added the TRPN gene nompC (no mechanoreceptor potential C), which was identified in neither dataset but is crucial for Drosophila auditory receptor function (22).…”
Section: Functional and Genetic Disruption Of The Sound-sensitive Ab mentioning
confidence: 99%
See 1 more Smart Citation
“…The ortholog of a key gene in the rhodopsin biosynthesis pathway santa-maria, Dvir\GJ17608, was up-regulated in both species in response to cold acclimation. Rhodopsin has long been known to be the primary pigment for phototransduction (see Katz and Minke (2009) for a review), however recently it has been shown that the rhodopsin signalling pathway also has a several additional lightindependent roles including hearing (Senthilan et al, 2012) and thermosensory signalling (Shen et al, 2011). Shen et al (2011) showed that by knocking out santa-maria in D. melanogaster, flies were unable to discriminate between differences in temperature.…”
Section: Functional Processesmentioning
confidence: 99%